2002
DOI: 10.1364/ao.41.004411
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced signal coupling into periodically poled lithium niobate with microlens arrays

Abstract: The return signal frequency of an eye-safe ladar system is upconverted from the infrared to the visible through sum-frequency generation by incorporation of periodically poled LiNbO3 into the receiver. A quantitative analysis of the angular acceptance and the quantum efficiency is then presented for a single macroscopic receiver optic and a multiaperture microlens array. Comparing both results, a 6x increase in the receiver field of regard and an 18% increase in beam coupling were realized for the microlens de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Since the sample light guide utilized consecutive structure of the conical channels, one might think of the MLA as a similar comparison (Fig. 6) [26][27][28]. Indeed MLA has been demonstrated to have the ability of focusing the light and enhancing the image quality, and it has been widely applied to delicate optical products.…”
Section: Resultsmentioning
confidence: 99%
“…Since the sample light guide utilized consecutive structure of the conical channels, one might think of the MLA as a similar comparison (Fig. 6) [26][27][28]. Indeed MLA has been demonstrated to have the ability of focusing the light and enhancing the image quality, and it has been widely applied to delicate optical products.…”
Section: Resultsmentioning
confidence: 99%
“…In this work we do not yet address this issue, but point to other work such as that by Brewer et al who demonstrated image upconversion using a multi-lens array to overcome the acceptance angle issues. 4,5,6 The experimental setup is shown in Figure 1. 3 µm pulses of light to simulate the LIDAR returns were generated from a seeded optical parametric generator (OPG).…”
Section: Optical Frequency Convertermentioning
confidence: 99%
“…2,3,4,5 The advantage of this scheme is that much higher sensitivity detectors may be used, including photon counting detectors. Detection technology in the near infrared (NIR) and visible is a much more mature technology than the mid-IR, and detection systems can take advantage of well-developed telecommunications technology.…”
Section: Introductionmentioning
confidence: 99%